Respuesta :
Answer:
k = -13/3 or ≈ -4.33
Step-by-step explanation:
-2= k+7/3
We can rewrite it for easy look:
k + 7/3 = -2
Subtract 7/3 from both side, we got:
k + 7/3 - 7/3 = -2 - 7/3
k + 0 = -2 - 7/3
Multiply -2 by 3 so it can subtract with - 7/3
k = -6/3 - 7/3
k = -13/3 or ≈ -4.33
-2= k+7/3
Move +7/3 to the other sign. Sign changes from +7/3 to -7/3.
-2-7/3=k+7/3-7/3
-2-7/3=k
find the common denominator for -2 which is 3.
Multiply by 3 for -2/1
(-2)(3)/1(3)
-6/3-7/3
=-13/3 or in mixed fraction - 4 1/3
Answer: k= -13/3 or k=-4 1/3